Policy–Practice Gaps in Extreme Poverty Alleviation: Evidence from South Bolaang Mongondow, North Sulawesi - Rares, Joyce Jacinta; Mamentu, Michael; Ridha, Muhammad; Abidin, Zainul (Journal of Cultural Analysis and Social Change, 2026)
This article examines the implementation of Indonesia’s extreme-poverty alleviation policy in South Bolaang Mongondow Regency, North Sulawesi, focusing on centrally funded programs that provide housing construction and residential land for households classified as extremely poor. Guided by Dunn’s policy-implementation lens covering policy action, regulative, allocation, agencies, program, and project the study adopts a qualitative descriptive design. Primary data were gathered through non-participant observation and in-depth interviews with key informants; secondary data consist of village and district policy documents. Findings indicate that, while the policy is associated with a downward trajectory in extreme-poverty incidence, program execution remains uneven. Targeting errors persist: benefits are frequently captured by kin networks of village elites and diverted to poor households that do not meet the “extreme” threshold. Across Dunn’s dimensions, the most salient gaps include ambiguous regulatory criteria, weak allocation procedures, fragmented inter-agency coordination, and limited project-level transparency and accountability. We conclude that effectiveness is constrained less by policy design than by implementation failures. Strengthening beneficiary identification, instituting public verification and transparent quotas, improving cross-agency data sharing, and embedding social audit and grievance-redress mechanisms are recommended to close the policy practice gap.